Discomfort in shoes through the perception of the elderly female public (ModaPalavra e-periódico, 2022)
Many elderly women have recurrent foot deformities due to inappropriate use of shoes and physiological changes resulting from aging. Thus, it is important to evaluate the feeling of discomfort in everyday footwear through the perception of the old user. The experimental research consisted of the application of a questionnaire to a sample of 135 elderly women, between 60 and 84 years old, separated by age group and socioeconomic classification, with objective questions and fields for comments, allowing to trace the profile of elderly women and their perception of discomfort related to footwear. The results showed significant data on the relationship between age and discomfort in the pants and interaction with the shoes, being possible to notice that most of the senscents express some difficulty in interaction with the product and that older women with older age report even more complaints, which reinforces the importance of developing footwear with an ergonomic approach directed appropriately to the elderly female public.
Keywords: Ergonomics; Shoes; Elferly women